Fiber-Based Laser Doppler Vibrometer for Middle Ear Diagnostics - Adam T. Waz; Marcin Masalski; Krzysztof Morawski (Photonics)
Laser Doppler vibrometry (LDV) is an essential tool in assessing by evaluating ossicle vibrations. It is used in fundamental research to understand hearing physiology better and develop new surgical techniques and implants. It is also helpful for the intraoperative hearing assessment and evaluation of postoperative treatment results. Traditional volumetric LDVs require access in a straight line to the test object, which is challenging due to the structure of the middle ear and the way the auditory ossicles are accessible. Here, we demonstrate the usage of a fiber-based laser Doppler vibrometer (FLDV) for middle ear diagnostics. Compared to classical vibrometers, the main advantages of this device are the ability to analyze several arbitrarily selected points simultaneously and the flexibility achieved by employing fiber optics to perform analysis in hard-to-reach locations, which are particularly important during endoscopic ear surgery. The device also allows for a simple change in measuring probes depending on the application. In this work, we demonstrate the properties of the designed probe and show that using it together with the FLDV enables recording vibrations of the auditory ossicles of the human ear. The obtained signals enable hearing analysis.